INTERCAMPUS SHUTTLE-RELATED TRANSPORTATION STRESS AMONG NIGERIAN UNIVERSITY STUDENTS: A LITERATURE REVIEW - Abubakar, Isah Funtua; Sabitu, Abdulmalik; Gyong, Yerima Emmanuel (African Journal of Social and Behavioural Sciences, 2025)
Transportation stress is a significant concern affecting university students worldwide, impacting their academic performance, mental well-being, and overall educational experience. This paper explores the causes of transportation stress among Nigerian university students. The methodology employed is the narrative approach to content analysis of relevant literature. Factors such as long commuting times, poor transportation infrastructure, financial constraints, and safety concerns are identified as primary contributors globally. In Nigeria, issues like inadequate inter-campus transportation, poor road conditions, rising transport costs, and insecurity exacerbate the problem. This paper concludes with recommendations for improving transport infrastructure, enhancing inter-campus services, and providing financial support to mitigate student transportation stress.